The Effect of Employee Motivation Towards Strategic Management : Case Study Among Middle Managers in Malaysian Banking Sector - Chong, Tze Tow (2017)
Banking industry is one of the country’s key economy drivers and acts as a control mechanism for the flow of capital. Thus, performance of banking industry has highly attracted concern from scholars, senior management, regulators and investors from the country. Middle management is the core pillar and successor of the senior management for the bank. The talents from this group are empowered to operate the bank’s core business and their performance will directly affect the banks’ performance. As a result of that banks’ performances are high associated with the middle management’s motivation and engagement aspects. Therefore, it is important for banks to retain them as they will bring the banks to move to next miles stone. Various factors influence the middle management’s motivation level which covers extrinsic value, intrinsic value, leadership, working environment, organizational culture, job security, career development, effective of communication, clear career path, participation in decision making, organization’s goal, branding and social opportunity. All these factors will result in high engagement which leads to an increase in employee performance, job satisfaction and high retention rate, reduction in absenteeism in organization, promotion on organization value and team harmony and elimination in the negative attitude of employees. This will benefit the banks’ bottom line by increasing productivity and reducing re-training cost. Consequently of that, Human Resource Management (HRM) plays an important role in driving employee motivation and employee engagement. The aim of this study is to examine the importance of employee motivation and employee engagement in the middle management of Malaysia banking industry and the relationship between employee motivation and employee engagement. This study found that employee motivation and employee engagement were important to middle management in the Malaysia banking industry. On top of that, it indicated that the relationship between employee motivation and employee engagement were moderate positive correlation. Therefore, 14 recommendations which include the priority and rollout plan are presented for senior management in Malaysia banking industry to enhance their middle management’s engagement strategy.